PENINGKATAN PENGETAHUAN SISWA SEKOLAH MENENGAH PERTAMA TENTANG PEMASANGAN DAN EFEK SAMPING ALAT ORTODONTI CEKAT - Nugroho Ahmad Riyadi; Thahirah Syafitri; Dharma Satya Aprianto; Chaerita Maulani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Malocclusion, or dental occlusion disorder, is one of the main factors disrupting the function of the oral cavity, especially the function of mastication. Malocclusion can be treated using orthodontic appliances. Orthodontic appliances are sometimes used not only for the benefit of dental treatment but as mere fashion due to a lack of knowledge, causing negative effects. Incompetent operators and poor maintenance procedures in orthodontic treatment will have a detrimental impact. Aims: The objective was to determine the knowledge level of junior high school students about the side effects of using fixed orthodontic appliances and the treatment of fixed orthodontic appliances by general dentists, orthodontists, and dental specialists. Methods: The type of research used is quasi-experimental, with one group and two measurements (pretest and post-test). Participants in this study were junior high school students in Central Jakarta. The sampling technique used total sampling. Data collection techniques using a questionnaire and analysis of data using the Wilcoxon Test P<0.05 are considered significant. The total number of students included in the study was 344. Result: There was a significant difference in student knowledge between the pretest and post-test after receiving an explanation among junior high school students (p<0.05). Conclusion: A fixed orthodontic treatment case was determined to be treated by an orthodontic specialist, and the general dentist has a limited range of cases treated with removable orthodontic appliances. Dental artisans can legally only treat removable dental prostheses. This information was conveyed to junior high school students; hence, they have been cautioned about choosing the right operator.